Perbandingan kadar albumin, proteintotal, urea, asam urat darah dan rasio urea/kreatinin urin sebelum dan sewaktu puasa ramadhan = Comparation of Blood Albumin, Total Protein, Uric Acid and Urinary Urea/Creatinin ... - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2001)
ABSTRACT During Ramadhan fasting adult human's body mainly uses gluconeogenesis process to produce glucose. This investigation was conducted to study the changes in plasma total protein, albumin, urea, uric acid and also urinary urea/creatinin ratio during Ramadhan fasting. Nineteen healthy students 19-22 years old, residing in a Pondok Pesantren Yogyakarta, volunteered to participate in the study. All of the subjects had similar types of activities and diet compositions. Blood samples were obtained from the subject on the 2nd day before Ramadhan and on the 28th day of Ramadhan and analyzed for the biochemical parameters. During the study total daily energy intake showed a significant decrease of calories (from 1902.93±468.08 Cal to 1718.31+341.76 Cal) and carbohydrate (from 391.94+6.62 g to 330.25+88.29 g). The percentage of calories showed a significant increase of fat (from 7.21+2.74 % to 10.18±4.24 % during Ramadhan). There are non significant changes in plasma urea (from 23.2+4.19 mg% to 22.3+4.67 mg%), plasma uric acid (from 5.55±0.91 mg% to 5.36+1.14 mg%), urea/creatinin urine ratio (from 9.1+7.54 to 7.94±2.81) and significant decreases (p